The medical profession and the universalisation of South African Health Care: analysing the response of Eastern Cape general practitioners to the National Health Insurance proposals - Hannah, Bridget (Rhodes University, Faculty of Humanities, Institute of Social and Economic Research, 2017)
In 2011, the Green Paper on National Health Insurance (NHI) in South Africa was released, committing the South African government to a 14-year plan to radically transform the currently inequitable health system towards providing comprehensive quality health care free at point of access to all citizens. The pursuit of universal health coverage (UHC) in South Africa forms part of a global aspiration to achieve more equitable healthcare delivery. One of the critical issues emerging from the Green Paper was how the NHI would be staffed. The NHI is unlikely to be adequately staffed without GPs but evidence suggests that private sector doctors have always been resistant to nationalisation or socialisation as a threat to their occupational power and professional status. The core work of this thesis is a study undertaken of 78 doctors in the Eastern Cape, focusing on private sector general practitioners (GPs), as the largest constituency of medical professionals in the country. The interview schedule was designed to gauge doctors' responses to the NHI, encourage discussion on their reactions to the reforms, and its implications in their view for private medical practice. The responses of the doctors are analysed through application of two theoretical themes, namely: (i) actor-centred policy creation, discussed through application of Walt and Gilson's (1994) shared focus on content, context, process and actors in the policy process, and (ii) the debate on medical professionalism, espoused by Freidson (1973, 1994) and argued against by Haug and Sussman (1969), and McKinlay (1972, 1993). Thus, if the process of policy making must take into account key actors in order to deliver a successful policy transition, what are the implications if these actors are actively excluded, or do not willingly cooperate? Does this indicate anything telling about the private sector's role to play in the pursuit of universal healthcare?
Keywords: Health insurance -- South Africa; Health insurance -- Government policy -- South Africa; Medical care, Cost of -- South Africa; National health insurance -- South Africa; Medical policy -- South Africa; Physicians -- South Africa -- Attitudes